ICTs and tourists’ satisfaction. A test on a rural tourist destination - Abang Azlan, Mohamad; May-Chiun, Lo; Peter, Songan; Alvin Wee, Yeo (e-Review of Tourism Research, 2010)
This study examines the impact of ICTs in local communities. This study was conducted in Bario, a rural tourism destination located in the state of Sarawak, Malaysia. The results indicate that ICTs are able to increase the number of visitors. The study also demonstrates the important dimensions that contribute to tourists’ satisfaction so that future ICT efforts can be focused on them. The findings revealed that most of the visitors were aware of Bario because of its publicity through the website.